Strengthening Bali's Reserve Economic Base: The Identification Made Pre And During Pandemic - Nanang Syaifudin; Syofriza Syofyan; Jakaria Jakaria; Lavlimatria Esya; Muhammad Yudhi Lutfi (LAFADZ JAYA Publisher, 2022)
Bali is the province hardest strike by the Covid-19 pandemic. The drying up of tourist arrivals strike accommodation and transportation businesses. Until now, the government has not heard any special actions to restore that’s Indonesian tourism icon. Therefore, in a decentralized system, understanding the economic characteristics of a region is important to increase economic productivity to make it more optimal. In this regard, this analysis aims to provide an overview of the economic characteristics in the province of Bali before the pandemic and during the pandemic and identify potential sectors that need to be developed. This study uses the Location Quotient, Shift-Share, Klassen Typology, and Overlay analysis methods from 2010 to 2021. From the results of the research, Bali Province before the pandemic had five leading sectors, but during the pandemic, Bali Province did not move only one base sector can become a mainstay, further innovation strategies are needed to stimulate Bali's economy to rise to the way it was before the pandemic. It takes the right policies from the Central and Regional Governments to make innovations and strategies so that the Bali economy returns to what it was before the pandemic.